KARAKTERISTIK PERSONAL SEBAGAI PEMODERASI PENGARUH PENGANGGARAN PARTISIPATIF DAN KETERLIBATAN KERJA PADA SENJANGAN ANGGARAN - Anggariani Putri, Putu Aninsa; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This research aimed to investigate the influence of participatory budgeting, and job involvement on budgetary slack, with personal characteristics as a moderating influence participatory budgeting and job involvement of the budgetary slack. The population in this study were all officers/employees who are directly involved in the preparation of the budget in Village Credit Institutions (LPDs) in Denpasar. This study uses purposive sampling method. Data are collected by using questionnaires. The data analysis technique used in this research is moderated regression analysis (MRA). The results shows that participatory budgeting has positive influence on budgetary slack. Work engagement negatively affect budgetary slack. Personal characteristics weaken the impact of participatory budgeting and job involvement on budgetary slack in LPDs Denpasar.
Keywords: participatory budgeting, job involvement, personal characteristics, budgetary slack